Respiratory symptoms of Swiss people with primary ciliary dyskinesia. Issue 2 (11th April 2022) - Goutaki, Myrofora; Hüsler, Leonie; Lam, Yin Ting; Koppe, Helena M.; Jung, Andreas; Lazor, Romain; Müller, Loretta; ,; Pedersen, Eva S.L.; Kuehni, Claudia E.
Background: Mostly derived from chart reviews, where symptoms are recorded in a nonstandardised manner, clinical data about primary ciliary dyskinesia (PCD) are inconsistent, which leads to missing and unreliable information. We assessed the prevalence and frequency of respiratory and ear symptoms and studied differences by age and sex among an unselected population of Swiss people with PCD. Methods: We sent a questionnaire that included items from the FOLLOW-PCD standardised questionnaire to all Swiss PCD registry participants. Results: We received questionnaires from 74 (86%) out of 86 invited persons or their caregivers (median age 23 years, range 3–73 years), including 68% adults (≥18 years) and 51% females. Among participants, 70 (94%) reported chronic nasal symptoms; most frequently runny nose (65%), blocked nose (55%) or anosmia (38%). Ear pain and hearing problems were reported by 58% of the participants. Almost all (99%) reported cough and sputum production. The most common chronic cough complications were gastro-oesophageal reflux (n=11; 15%), vomiting (n=8; 11%) and urinary incontinence (n=6; 8%). Only nine (12%) participants reported frequent wheeze, which occurred mainly during infection or exercise, while 49 (66%) reported shortness of breath, and 9% even at rest or during daily activities. Older patients reported more frequent nasal symptoms and shortness of breath. We found no difference by sex or ultrastructural ciliary defect. Conclusion: This is the first study to describe patient-reported PCD symptoms. The consistent collection of standardised clinical data will allow us to better characterise the phenotypic variability of the disease and study disease course and prognosis. Detailed information about patient-reported PCD symptoms will help characterise the phenotypic variability of the disease and could inform the development of individualised treatment strategies for patients https://bit.ly/363Zb4T